Orbital Hydatid Cyst: An Interventional Case Series: http://doi.org/10.36351/pjo.v37i2.1147 - Khan, Tajamul; Hussain, Ibrar; Shah, Zaman (Pakistan Journal of Ophthalmology, 2021)
Purpose: To find out the demographics, presentation, and outcome of surgical treatment in patients of orbital hydatid cyst. Study Design: Interventional case series. Place and Duration of Study: Khyber Teaching Hospital Peshawar, Pakistan from 2009 to 2019. Methods: This study included 11 patients with orbital hydatid cyst who presented in Khyber Teaching Hospital, Peshawar. Detailed history, ocular examination and Orbital imaging (Ophthalmic B-Scan, CT scan and/or MRI) was performed. The patients underwent Orbitotomy, cyst extirpated and sent for histopathology. Albendazole was given to the patients for 12 weeks after surgery. The preoperative and postoperative data until last follow-up was analyzed. Results: Male to Female ratio was 5:6 and the mean age of the patients was 18.17 ± 17.4 years. Mean amount of proptosis was 26.27 ± 2.05mm and visual acuity was 0.23 ± 0.33 decimal in the affected eye at presentation. Eight patients (72.8%) had Relative Afferent Pupillary Defect with swollen discs. After imaging studies, presumptive diagnosis of hydatid cyst was made. Histopathology confirmed the diagnosis of hydatid cyst in all cases. Mean proptosis at the last follow up improved to 19.04 ± 1.45mm (P value = 0.00) and visual acuity to 0.47 ± 0.22 decimals (P value = 0.048). Only one patient (9.1%) had an associated hydatid cyst in the lung. There was no recurrence until last follow-up. Conclusion: Hydatid cyst should be considered in differential diagnosis of proptosis in patients under 20. Surgical excision followed by a course of oral Albendazole is effective for the treatment of orbital hydatid cyst. Key Words: Orbital hydatid cyst, Proptosis, Orbitotomy.